THE COMPARATIVE ANALYSIS OF ISLAM BANKING PERFORMANCE IN TERMS OF CAMEL AND RGEC IMPLEMENTATION - Zein, Aliman Syahuri (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This study aims to analyze the comparative performance of Islamic banking in terms of the application of CAMEL and RGEC. The bank soundness indicators used for the RGEC method consist of; risk profile (NPF), earnings (ROA), capital (CAR). Meanwhile, the CAMEL method consists of; capital (CAR), assets, earnings (ROA), and liquidity (represented by FDR). Data was obtained from the official website of the OJK, www.ojk.go.id and the official website of BI, namely www.bi.go.id. The sample used was 10 years, from 2011 to 2020. The statistical test used was the paired sample t test through the SPSS application, and descriptive analysis. The results of the study concluded that in general, Islamic banking for the last 10 years was declared healthy. It's just that when viewed from the indicators of risk profile, earnings, liquidity, there are differences in the bank soundness of Islamic banking using the RGEC and CAMEL methods. As for the CAR indicator, there is no difference. The bank soundness measured used by the RGEC method is carried out using a risk-based bank rating (RBBR) approach. This assessment is a comprehensive and structured assessment of the results of the integration between risk and performance profiles which includes the implementation of good governance, profitability, and capital. So that the OJK as a supervisor can carry out appropriate and timely supervision, because the assessment is carried out comprehensively on all assessment factors and is focused on significant risks and can be immediately communicated to the bank in order to determine follow-up supervision